2018
DOI: 10.1016/j.jana.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The State of Adherence to HIV Care in Black Women

Abstract: The purpose of this systematic review was to assess the state of adherence to HIV care such as HIV medication and appointment adherence among Black women in the United States. After a systematic search of CINAHL, PubMed, EMBASE, and clinicialtrials.gov, 26 studies and two ongoing trials met inclusion criteria. Psychosocial factors such as intersectional stigmas and depression were among the salient factors associated with adherence-to-care behaviors in women living with HIV (WLWH). In addition, interpersonal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…4 These disparities continue across the treatment cascade for women with HIV in the United States with black women having lower treatment engagement, retention, and adherence. [5][6][7] Ongoing disparities in these areas for black women may be due to adversities such race-and HIV-related discrimination and microaggressions that contribute to barriers to receiving HIV-related care. However, no existing literature has explored how these factors relate to barriers to HIV-related care among black women living with HIV (BWLWH).…”
Section: Introductionmentioning
confidence: 99%
“…4 These disparities continue across the treatment cascade for women with HIV in the United States with black women having lower treatment engagement, retention, and adherence. [5][6][7] Ongoing disparities in these areas for black women may be due to adversities such race-and HIV-related discrimination and microaggressions that contribute to barriers to receiving HIV-related care. However, no existing literature has explored how these factors relate to barriers to HIV-related care among black women living with HIV (BWLWH).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, African American WLWH in the South said it was also important that their health care provider takes a genuine interest in their care. 10 Project THANKS focus groups reinforced these findings.…”
Section: How Does Your Research Contribute To the Field?mentioning
confidence: 79%
“…A systematic review by Lambert et al found that social support was a valuable resource that improved ART adherence and retention in care. 10 Similarly, Project THANKS participants indicated that it was comforting to connect with other WLWH. Social support was a major theme that arose from the qualitative study.…”
Section: How Does Your Research Contribute To the Field?mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal ART regimens to achieve durable viral load suppression are essential for the survival of PLWH. Yet, most clinical trials have enrolled majority male samples (Lambert et al, 2018), despite ample evidence that women have unique needs requiring tailored intervention. Because clinical trials are the gold standard for determining the safety, efficacy, and effectiveness of medical and behavioral interventions, greater inclusion of women participants is needed to determine their effects on women's health outcomes.…”
Section: Biomedical Interventions For Womenmentioning
confidence: 99%